Comprehensive Genomic Profiling Aids in Distinguishing Metastatic Recurrence from Second Primary Cancers. (18th September 2017) - Weinberg, Benjamin A.; Gowen, Kyle; Lee, Thomas K.; Ou, Sai‐Hong Ignatius; Bristow, Robert; Krill, Lauren; Almira‐Suarez, M. Isabel; Ali, Siraj M.; Miller, Vincent A.; Liu, Stephen V.; Klempner, Samuel J.
Abstract : Background: Metastatic recurrence after treatment for locoregional cancer is a major cause of morbidity and cancer‐specific mortality. Distinguishing metastatic recurrence from the development of a second primary cancer has important prognostic and therapeutic value and represents a difficult clinical scenario. Advances beyond histopathological comparison are needed. We sought to interrogate the ability of comprehensive genomic profiling (CGP) to aid in distinguishing between these clinical scenarios. Materials and Methods: We identified three prospective cases of recurrent tumors in patients previously treated for localized cancers in which histologic analyses suggested subsequent development of a distinct second primary. Paired samples from the original primary and recurrent tumor were subjected to hybrid capture next‐generation sequencing‐based CGP to identify base pair substitutions, insertions, deletions, copy number alterations (CNA), and chromosomal rearrangements. Genomic profiles between paired samples were compared using previously established statistical clonality assessment software to gauge relatedness beyond global CGP similarities. Results: A high degree of similarity was observed among genomic profiles from morphologically distinct primary and recurrent tumors. Genomic information suggested reclassification as recurrent metastatic disease, and patients received therapy for metastatic disease based on the molecular determination. Conclusions: Our cases demonstrate an important adjunct role for CGP technologies in separating metastatic recurrence from development of a second primary cancer. Larger series are needed to confirm our observations, but comparative CGP may be considered in patients for whom distinguishing metastatic recurrence from a second primary would alter the therapeutic approach. Abstract : Distinguishing metastatic recurrence from the development of a second primary cancer has important prognostic and therapeutic value and represents a difficult clinical scenario. Advances beyond histopathological comparison are needed. This article reports on the ability of comprehensive genomic profiling (CGP) to aid in distinguishing between these clinical scenarios.